PENGARUH KEPEMIMPINAN KEPALA SEKOLAH TERHADAP KINERJA GURU SEKOLAH SMP NEGERI I CEMPA KABUPATEN PINRANG - Sadariah Sadariah (AkMen JURNAL ILMIAH, 2018)
Good principal leadership can be the main driving force in supporting effective and efficient education in schools. Objective conditions need to be assessed in order to measure the extent of the implementation of the task of teachers in schools, given the implementation of these tasks can be influenced by several factors. This study aims to: Describe the leadership of the principal, to the performance of teachers in SMP NEGERI I CEMPA Pinrang District, analyzing the partial influence of leadership of the principal on the performance of teachers in SMP NEGERI I CEMPA Pinrang Regency, This study used a quantitative approach with data collection techniques through questionnaires on 45 teachers as population and also as sample of research. Test requirements analysis is done through linearity test, while the data is analyzed descriptively and hypothesis test with multiple regression. The results show that (1) principal leadership and teacher performance are generally in very good category, (2) Leadership of principals gives positive influence to teacher performance. The higher the leadership of the principal, the more the teacher performance in SMP Negeri I CEMPA Pinrang District